Penyuluhan dalam Pemanfaatan E-Commerce Digital Wallet, dan Online Delivery di era digitalisasi - Dian Rachmawati Afandi; Indra Permana; Dwi Astuti; Arif Widodo Nugroho (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The research explores the role of digital wallets and online delivery services in enhancing the competitive edge of Micro, Small, and Medium Enterprises (MSMEs) amidst rapid digitalization. With the growing importance of social capital and technological adoption, MSMEs can expand their business reach and improve their performance. The study highlights the significant increase in digital wallet utilization in Indonesia, where numerous platforms like Gopay and OVO have gained traction. Challenges such as a lack of digital literacy among MSME owners hinder their ability to leverage e-commerce effectively. This project involved direct support and consultation for MSMEs, aiming to address their challenges and identify strategic solutions. Findings indicate improved customer engagement through digital marketing, which allows MSMEs to build brand awareness without the need for extensive resources. Ultimately, the study advocates for increased digital presence and adaptability among MSMEs to thrive in the evolving market landscape.